Dampak Kualitas Pelayanan, Persepsi Nilai Serta Citra Perusahaan Terhadap Peningkatan Kepuasan Pelanggan Bandar Udara Internasional Sentani-Jayapura - Kandius Wandik (Journal of Management and Bussines (JOMB), 2023)
The aim of this research is to see how big a role service quality, company image and perceived value play in customer satisfaction at Sentani-Jayapura International Airport. This research uses a quantitative approach using SEM-PLS analysis. The research results show that there is a significant influence of Service Quality and Value Perception on Customer Satisfaction through Company Image. Conclusion, Service Quality and Perceived Value of Customer Satisfaction and Company Image are important aspects in increasing customer satisfaction. Keywords: Company Image, Service Quality, Perceived Value, Customer Satisfaction